Porous silk fibroin microspheres as well as preparation method and application thereof

By using hydrophilic inducers to regulate the self-assembly of silk fibroin, high-purity porous silk fibroin microspheres were prepared, which solved the problems of high energy consumption and potential toxicity in the existing technology and achieved biocompatibility and wide application.

CN120757837APending Publication Date: 2025-10-10WUHAN TEXTILE UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510657458.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing methods for preparing porous silk fibroin microspheres require strict low-temperature conditions, high energy consumption, and the possible introduction of toxic reagents, which are potentially toxic and limit their scope of application.

Method used

An inducer containing hydrophilic functional groups is mixed with the silk fibroin solution to form porous microspheres through self-assembly. The intermolecular interactions are regulated during the concentration-film formation process. The inducer is then removed and the solution is dried to form high-purity porous microspheres.

Benefits of technology

The preparation process is simple and does not use toxic reagents. The obtained porous silk fibroin microspheres have a high specific surface area and good biocompatibility, and are suitable for cell culture carriers, drug delivery systems, and protein separation and purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757837A_ABST
    Figure CN120757837A_ABST
Patent Text Reader

Abstract

The invention provides porous silk fibroin microspheres as well as a preparation method and application thereof, and belongs to the technical field of biomedical materials. According to the method, a high-molecular compound containing a hydrophilic functional group is selected as a specific inducer, a silk fibroin solution and the specific inducer are blended, the intermolecular interaction of silk fibroin is regulated and controlled under the action of the inducer, and a large number of silk fibroin microspheres which are uniform in size and stable in structure are formed in a self-assembly mode in the concentration-film forming process. On the basis, the inducer is removed, and then drying treatment is performed to form the porous silk fibroin microspheres with high purity and high specific surface area. The preparation process is simple, no toxic reagent is used in the preparation process, and the obtained silk fibroin microspheres can be applied to the fields of cell culture carriers, drug delivery systems, protein separation and purification and the like and have wide application prospects in the field of biomedical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to porous silk fibroin microspheres and a preparation method and application thereof. Background Art

[0002] With the rapid development of biomaterials science, biocompatible, biodegradable natural polymers are increasingly being used in areas such as drug delivery and tissue engineering. Silk fibroin (SF), a natural protein extracted from silk, is a highly sought-after natural polymer material with excellent mechanical strength, physicochemical properties, and biocompatibility.

[0003] Porous microspheres have a high specific surface area and good biocompatibility, so they have a wide range of applications in the biomedical field. Most of the current methods for making porous silk fibroin microspheres are based on adding pore-forming agents or other chemical substances to make a porous structure appear on the surface of the microspheres. For example, the patent with publication number CN108553690A proposes a strontium-doped porous silk fibroin microsphere and its preparation method. The patent proposes a strontium-doped porous silk fibroin microsphere for bone repair, combining the biocompatibility of silk fibroin (SF) and the osteogenic induction ability of strontium (Sr), and preparing microspheres with high porosity (>80%) and controllable pore size (5-40μm) by emulsion freeze-drying, and realizing the sustained release of strontium ions. However, this method requires strict pre-cooling under low temperature conditions (-30 to -50°C) to remove petroleum ether, which has high energy consumption, and the long-term accumulation of strontium ions may be potentially toxic.

[0004] In view of this, it is necessary to design a preparation method for porous silk fibroin microspheres with simple process, high ball formation rate, and no introduction of other difficult-to-volatilize and toxic reagent doping substances during the preparation process to solve the above problems. Summary of the Invention

[0005] In view of the defects of the above-mentioned prior art, the object of the present invention is to provide a porous silk fibroin microsphere and its preparation method and application. The preparation method comprises mixing a silk fibroin solution with a specific inducer, utilizing the effect of the inducer to regulate the intermolecular interaction of the silk fibroin, and self-assembling to form a large number of silk fibroin microspheres with relatively uniform size and stable structure during the concentration-film formation process. On this basis, the inducer is removed and then dried to form porous silk fibroin microspheres with high purity and high specific surface area. The preparation process of the present invention is simple, and no toxic reagents are used in the preparation process. The obtained silk fibroin microspheres can be applied to fields such as cell culture carriers, drug delivery systems, protein separation and purification, and have broad application prospects in the field of biomedical materials.

[0006] To achieve the above object, the present invention provides a method for preparing porous silk fibroin microspheres, comprising the following steps:

[0007] S1, respectively, prepare a silk fibroin solution, an aqueous solution of an inducing agent for standby; the inducing agent contains a hydrophilic functional group;

[0008] S2, the prepared silk fibroin solution is mixed with the solution property inducing agent, and stirring to obtain a mixed solution;

[0009] S3, the obtained mixed solution is concentrated and film forming to obtain a film containing silk fibroin microspheres;

[0010] S4, the obtained film is dissolved and centrifuged, and after drying, porous silk fibroin microspheres are obtained.

[0011] Further, in step S1, the inducing agent is one of sodium hyaluronate, sodium alginate, carboxymethyl cellulose, polyethylene glycol, polyvinyl alcohol, polypropylene glycol, polylactic acid and polycaprolactone.

[0012] Further, in the mixed solution of step S2, the volume ratio of the silk fibroin solution to the aqueous solution of the inducing agent is 1:(0.25-5); wherein the mass fraction of silk fibroin is 0.5-5%, and the mass fraction of the inducing agent is 0.5-5%.

[0013] Further, the mass percentage of the silk fibroin solution is 1-10wt%, and the mass percentage of the aqueous solution of the inducing agent is 1-10wt%.

[0014] Further, the drying treatment method is natural drying or vacuum drying at 37-60℃, or reduced pressure freeze drying at-45--60℃.

[0015] Further, in step S3, during the concentration-film forming treatment, the temperature is 10-120℃, and the time is at least 6h.

[0016] Further, it further comprises soaking the obtained porous silk fibroin microspheres in ethanol, then removing the ethanol by centrifugation, and resuspending twice with water.

[0017] To achieve the above-mentioned purpose, the application further provides a porous silk fibroin microsphere, which is prepared by the preparation method of any one of the preceding technical solutions.

[0018] Further, the porous silk fibroin microspheres are regular spherical or near-spherical, the particle size range is 3-15μm, and the surface has a porous structure with a pore size of less than 500nm.

[0019] The aforementioned porous silk fibroin microspheres can be used in the fields of cell culture carriers, drug delivery systems and protein separation and purification.

[0020] The application has the following beneficial effects:

[0021] 1. The preparation method of porous silk fibroin microspheres provided by the present invention comprises selecting a polymer compound containing hydrophilic functional groups as a specific inducer, blending a silk fibroin solution with the specific inducer, utilizing the effect of the inducer to regulate the intermolecular interaction of the silk fibroin, and self-assembling to form a large number of silk fibroin microspheres with relatively uniform size and stable structure during the concentration-film formation process. Inducers such as sodium hyaluronate, polyethylene glycol, sodium alginate and other substances contain a large number of hydrophilic functional groups (such as carboxyl groups, hydroxyl groups, ether bonds, etc.), which can bind to the hydroxyl groups, amino groups, and carboxyl groups of the silk fibroin through hydrogen bonds, induce the silk fibroin to self-assemble into microspheres, and then improve the hydration capacity of the microsphere surface. On this basis, the inducer is removed, and then dried to form porous silk fibroin microspheres with high purity and high specific surface area. The preparation process of the present invention is simple, and no toxic reagents are used in the preparation process. The obtained silk fibroin microspheres can be applied to fields such as cell culture carriers, drug delivery systems, protein separation and purification, and have broad application prospects in the field of biomedical materials.

[0022] 2. The inducing agent used in the present invention contains hydrophilic functional groups. Due to its large number of hydroxyl groups in its structure, it has strong water-binding ability. It can bind with water molecules in the silk fibroin solution, inducing the silk fibroin to form a stable structure through self-assembly, which imparts good mechanical properties and stability to the material. The resulting porous microspheres have a high specific surface area and good biocompatibility, and therefore have wide applications in the biomedical field.

[0023] 3. The method for preparing porous silk fibroin microspheres provided by the present invention can adjust the size of the microspheres and the pore size by adjusting the ratio of the inducer concentration to the silk fibroin and the drying conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a flow chart of the method for preparing porous silk fibroin microspheres of the present application.

[0025] Figure 2 This is an electron microscope morphology of the porous silk fibroin microspheres prepared in Example 1.

[0026] Figure 3 This is an optical microscope morphology of the porous silk fibroin microspheres prepared in Example 1.

[0027] Figure 4 This is the infrared spectrum of the porous silk fibroin microspheres prepared in Example 1.

[0028] Figure 5 This is the XRD pattern of the porous silk fibroin microspheres prepared in Example 1.

[0029] Figure 6An electron microscope morphology diagram of the porous silk fibroin microspheres prepared for Example 2.

[0030] Figure 7 An electron microscope morphology diagram of the porous silk fibroin microspheres prepared for Comparative Example 1.

[0031] Figure 8 An electron microscope morphology diagram of the porous silk fibroin microspheres prepared for Example 3.

[0032] Figure 9 An electron microscope morphology diagram of the porous silk fibroin microspheres prepared for Comparative Example 2.

[0033] Figure 10 An optical microscope morphology diagram of the porous silk fibroin microspheres prepared for Example 7.

[0034] Figure 11 An optical microscope morphology diagram of the porous silk fibroin microspheres prepared for Example 8.

[0035] Figure 12 An optical microscope morphology diagram of the porous silk fibroin microspheres prepared for Example 9.

[0036] Figure 13 An electron microscope morphology diagram of the porous silk fibroin microspheres prepared for Example 10. DETAILED DESCRIPTION

[0037] In order to make the purposes, technical solutions and advantages of the present application clearer, the present application will be described in detail below with reference to the drawings and specific examples.

[0038] In addition, it should also be noted that the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such process, method, article or equipment.

[0039] In the prior art, a pore-forming agent is added to make the surface of the microspheres have a porous structure. However, the porous silk fibroin microspheres prepared by this method may have potential toxicity, do not have biocompatibility, and have limited use range.

[0040] Referring to Figure 1 The present application provides a preparation method of porous silk fibroin microspheres, which comprises the following steps:

[0041] S1, respectively preparing a silk fibroin solution and an aqueous solution of an inducing agent for standby use;

[0042] The mass percentage of the silk fibroin solution is 1-10wt%.

[0043] The mass percentage of the inducer aqueous solution is 1-10wt%.

[0044] Among them, the inducer is a high molecular compound containing hydrophilic functional groups (such as hydroxyl, carboxyl, ether bonds, etc.) and having good water solubility and biocompatibility, such as sodium hyaluronate, sodium alginate, carboxymethyl cellulose, polyethylene glycol, polyvinyl alcohol, polypropylene glycol, polylactic acid, polycaprolactone, etc.

[0045] The preparation method of the silk fibroin solution comprises the following steps:

[0046] Natural silk is obtained, and the natural silk is placed in a Na2CO3 solution for degumming. The degummed silk is washed and dried at 60°C to obtain pure silk fibroin fibers. Then, the silk fibroin fibers are dissolved in a lithium bromide solution or a ternary solution, and dialyzed to obtain a silk fibroin solution.

[0047] The preparation process of the inducer aqueous solution is: mixing the inducer with water, placing the mixture on a magnetic stirrer and stirring for a certain period of time to prepare a uniform inducer aqueous solution.

[0048] S2, mixing the prepared silk fibroin solution with a solution property inducer, and stirring to obtain a mixed solution;

[0049] In the mixed solution, the volume ratio of the silk fibroin solution to the inducer aqueous solution is 1:(0.25-5).

[0050] The mass fraction of the silk fibroin is 0.5-5%, and the mass fraction of the inducer is 0.5-5%.

[0051] Stir the mixture in a magnetic stirrer for 5-60 minutes to ensure that the silk fibroin solution and the inducer are fully mixed in the blend system to ensure that well-dispersed and uniform porous silk fibroin microspheres can be formed in the subsequent ball-forming process. Excessive inducer concentration will cause the formed microspheres to aggregate severely, and it will not be possible to obtain well-dispersed microspheres.

[0052] S3, concentrating and film-forming the obtained mixed solution to obtain a film containing silk fibroin microspheres;

[0053] During the concentration-film forming treatment, the temperature is 10-120° C. and the time is at least 6 hours.

[0054] During this process, the inducer contains a large number of hydroxyl groups. As the concentration progresses, the water molecules in the inducer evaporate and decrease, competing with the water molecules in the silk fibroin, inducing the silk fibroin macromolecules to self-assemble into microspheres. The subsequent centrifugal washing process can remove unreacted inducer. Even if the washing process is not thorough and a small amount of residue remains, due to the good biocompatibility of the selected inducer, it has no adverse effect on product performance.

[0055] S4, dissolving the obtained membrane and centrifuging it, and then drying it to obtain porous silk fibroin microspheres.

[0056] Centrifugation can remove unreacted substances and make the microspheres more evenly dispersed, reducing adhesion.

[0057] Drying treatment involves natural drying at 37-60°C or vacuum drying, or freeze drying at -45-60°C under reduced pressure. This method preserves the material's pre-drying morphology, resulting in microspheres that most closely resemble those in solution. Consequently, the resulting porous silk fibroin microspheres exhibit a regular spherical or nearly spherical shape.

[0058] The surface pore structure of silk fibroin microspheres can be adjusted by using different drying conditions.

[0059] Specifically, the pore size of the microspheres obtained under natural drying conditions (37°C to 60°C) is in the range of about 100 to 200 nm, and the pores on the surface of the microspheres are relatively dense.

[0060] The pore size of the microspheres obtained under vacuum drying conditions (37°C to 60°C) is slightly reduced, ranging from about 100 to 150 nm, and the surface of the microspheres has a uniform pore structure. Under freeze-drying conditions (-45°C to -60°C), the ice crystals are confined in the frozen phase, resulting in a smaller pore structure on the surface of the microspheres, with a pore size range of less than 100 nm.

[0061] Preferably, the obtained porous silk fibroin microspheres can be immersed in ethanol, then centrifuged to remove the ethanol, and resuspended twice in water. In this way, the two water resuspensions remove the residual ethanol inside the microspheres and restore their surface hydrophilicity to ensure the dispersibility of the microspheres in a physiological environment.

[0062] The porous silk fibroin microspheres prepared by the above scheme are regular spherical or nearly spherical, with a particle size range of 3 to 15 μm; the surface has a porous structure, and the pore size is within 500 nm.

[0063] The porous silk fibroin microspheres can be used in cell culture carriers, drug delivery systems, and the fields of protein separation and purification.

[0064] The preparation method of the porous silk fibroin microspheres provided by the present invention is described below with reference to specific examples.

[0065] Example 1

[0066] The present embodiment provides a method for preparing porous silk fibroin microspheres, comprising the following steps:

[0067] S1, preparing a silk fibroin solution for standby;

[0068] The natural silk is placed in a 0.1wt% Na2CO3 solution for boiling treatment for 60 min, repeated twice, and then placed in a 0.05wt% Na2CO3 solution for boiling treatment for 60 min to remove sericin. The degummed silk is washed and dried, and then added to a 9.3mol / L LiBr solution at a ratio of 1:5 for dissolution. Subsequently, it is transferred to a dialysis bag and dialyzed in a 4°C refrigerator for 3 days. After centrifugation, a silk fibroin solution is obtained, and the mass fraction is measured to be 4%.

[0069] Preparation of a sodium hyaluronate solution for standby:

[0070] 1g of sodium hyaluronate is weighed and added to 25ml of deionized water. After slow stirring for 1h, a sodium hyaluronate solution with a mass fraction of 4% is obtained.

[0071] S2, mixing the prepared silk fibroin solution with a solution property inducer, and stirring to obtain a mixed solution. In the mixed solution, the volume ratio of the silk fibroin solution to the sodium hyaluronate solution is 1:1. In the mixed solution, the mass fraction of silk fibroin is 2%, and the mass fraction of sodium hyaluronate is 2%.

[0072] S3, placing the obtained mixed solution into a 60°C oven for concentration-film formation treatment for 6h to obtain a film containing silk fibroin microspheres;

[0073] S4, dissolving the obtained film in deionized water and centrifuging under the conditions of 4°C, 8000rpm, and 5min. The unreacted sodium hyaluronate is removed by washing with deionized water for three times. Subsequently, the microspheres are naturally dried at 60°C to obtain porous silk fibroin microspheres with a porous structure.

[0074] Figure 2 and Figure 3 The electron microscope morphology diagram and the optical microscope diagram of the porous silk fibroin microspheres prepared in Example 1 are shown. It can be seen that the microspheres have uniform size distribution, the particle size range is about 7-15μm, and the surface has a dense pore structure with a pore size of about 450nm.

[0075] Figure 4 and Figure 5The following are the infrared spectra and XRD patterns of the porous silk fibroin microspheres prepared in Example 1. The porous silk fibroin microspheres exhibit characteristic peaks at 1651 and 1532, with the 1651 peak corresponding to the protein's α-helical structure and the 1532 peak corresponding to the protein's β-sheet structure. XRD patterns also reveal characteristic peaks at 11.8°, 19.9°, and 28.2°, indicating that the porous silk fibroin microspheres are primarily composed of the Silk I structure.

[0076] FTIR and XRD analysis revealed that the porous silk fibroin microspheres exhibited a mixed conformation of α-helical and β-pleated sheets, with a predominantly Silk I-type crystalline structure. This structure imbued the microspheres with high swelling and controllable degradability.

[0077] Example 2

[0078] The only difference between Example 2 and Example 1 is the drying method. Specifically, the microspheres were pre-frozen at -20°C before freeze-drying, and then freeze-dried (i.e., dried at -50°C under reduced pressure for 12 hours).

[0079] Figure 6 This is an electron micrograph of the porous silk fibroin microspheres prepared in Example 2. As can be seen, the resulting silk fibroin microspheres exhibit a porous surface structure. Compared to natural drying, freeze-dried microspheres retain a porous surface structure and exhibit good dispersibility, but the surface pore structure is slightly smaller, with pore sizes within approximately 100 nm.

[0080] Because the resulting silk fibroin microspheres are negatively charged and lysozyme is positively charged at pH 7, the microspheres adsorb lysozyme via electrostatic adsorption. The adsorption capacity reached 76.98 mg / g after 8 hours, decreasing with time and gradually reaching equilibrium. This suggests that these porous microspheres could serve as a novel bioaffinity adsorption material suitable for protein separation and purification.

[0081] Comparative Example 1

[0082] The only difference between Comparative Example 1 and Example 2 is the different drying methods, specifically, freezing with liquid nitrogen (-196° C.) before freeze-drying, followed by freeze-drying (i.e., drying under reduced pressure at -50° C. for 12 h).

[0083] Figure 7 This is an electron microscope morphology of the porous silk fibroin microspheres prepared in Comparative Example 1.

[0084] From the comparison between Example 2 and Comparative Example 1, it can be seen that the microspheres prepared in Example 2 have obvious microporous structure and smooth surface, while the microspheres prepared in Comparative Example 1 have porous structure, but it can be obviously observed that some broken microspheres are distributed around the microspheres. This is because the microspheres prepared in Example 2 are placed in -20℃ for freezing before lyophilization, which is milder than the freezing in liquid nitrogen (-196℃), so that the porous microspheres have smooth surface distribution and no broken microspheres. In Comparative Example 1, the microspheres are frozen in liquid nitrogen, which increases the internal pressure of the microspheres, resulting in the broken microspheres.

[0085] Example 3

[0086] Example 3 is different from Example 1 in that after the fibroin microspheres are obtained by centrifugation according to the steps of Example 1, the microspheres are soaked in 75% ethanol for about 2h, the ethanol is removed by centrifugation, and the porous fibroin microspheres are obtained by natural drying at 60℃.

[0087] Figure 8 The electron microscope morphology of the porous fibroin microspheres prepared in Example 3 is shown. It can be seen that the microspheres soaked in 75% ethanol have better dispersibility, and the porous microspheres have smooth surface, pore size of about 200nm and are more dense.

[0088] Examples 4-6 and Comparative Example 2

[0089] Examples 4-6 and Comparative Example 2 are different only in that the mass fraction of the fibroin solution, the mass fraction of the inducer, and the volume ratio of the fibroin solution to the inducer aqueous solution in the mixed solution are changed, and the others are substantially the same as those in Example 1, which will not be repeated here.

[0090]

[0091] It can be known from the experiment that when the mass fraction of the mixed solution of the fibroin solution and the inducer solution is within 5%, the porous microspheres with uniform size and good dispersibility can be obtained, and the pore size of the microspheres is about 200nm. When the mass fraction of the inducer in the mixed solution is too high, the surface pore structure of the obtained microspheres is not obvious and the adhesion phenomenon is serious, as shown in Figure 9

[0092] Examples 7-10

[0093] Examples 7-10 are different from Example 1 only in that the type of the inducer is changed, and the others are substantially the same as those in Example 1, which will not be repeated here.

[0094]

[0095] ​Figure 10 and Figure 11 The optical microscopic morphology images of the porous silk fibroin microspheres prepared in Examples 7 and 8 are shown. It can be seen that after blending the silk fibroin solution with the polyethylene glycol / sodium alginate solution, silk fibroin microspheres with good dispersion can be obtained. When polyethylene glycol is used as an inducer, since polyethylene glycol is a hydrophilic substance, the ether bonds therein form hydrogen bonds with the polar groups of the silk fibroin, inducing the silk fibroin to assemble into microspheres during the concentration-film formation process.

[0096] When sodium alginate is used as an inducer, due to its inherent high viscosity, some of the microsphere surfaces may be coated with a layer of sodium alginate molecules, forming a composite structure (silk fibroin microspheres coated with a layer of sodium alginate molecules). As a natural polysaccharide material, sodium alginate has excellent biocompatibility, so this coating not only does not affect the biosafety of the microspheres, but also facilitates the formation of a pore structure during the drying process.

[0097] Figure 12 and Figure 13 The optical microscopic morphology and electron microscopic images of the porous silk fibroin microspheres prepared in Examples 9-10 are shown, respectively. It can be seen that as the concentration and ratio of polyethylene glycol increase, its flexibility leads to increased steric hindrance, resulting in smaller microspheres with a particle size range of approximately 3 to 5 μm. When the inducer is sodium alginate, due to its strong hydrophilicity and charge density, the microspheres formed during the concentration-film formation process have a smaller particle size, with a particle size range of approximately 4 to 7 μm.

[0098] Experiments have shown that porous silk fibroin microspheres can also be successfully prepared by replacing the inducer sodium hyaluronate with carboxymethyl cellulose, polyvinyl alcohol, polypropylene glycol, polylactic acid, and polycaprolactone.

[0099] In summary, the present invention provides a method for preparing porous silk fibroin microspheres. This method comprises blending a silk fibroin solution with a specific inducer, utilizing the effect of the inducer to regulate the intermolecular interactions of the silk fibroin, and self-assembling to form a large number of silk fibroin microspheres with uniform size and stable structure during the concentration-film formation process. On this basis, the inducer is removed by centrifugation, and then the product is dried to form porous silk fibroin microspheres with high purity and high specific surface area during the drying process. The preparation process of the present invention is simple, and no toxic reagents are used in the preparation process. The obtained silk fibroin microspheres can be used in the fields of cell culture carriers, drug delivery systems, protein separation and purification, and have broad application prospects in the field of biomedical materials.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing porous silk fibroin microspheres, characterized in that: The following steps are involved: S1, preparing a silk fibroin solution and an inducer aqueous solution respectively for later use; the inducer contains a hydrophilic functional group; S2, mixing the prepared silk fibroin solution with a solution property inducer, and stirring to obtain a mixed solution; S3, concentrating and film-forming the obtained mixed solution to obtain a film containing silk fibroin microspheres; S4, dissolving the obtained membrane and centrifuging it, and then drying it to obtain porous silk fibroin microspheres.

2. The method for preparing porous silk fibroin microspheres according to claim 1, wherein: In step S1, the inducer is one of sodium hyaluronate, sodium alginate, carboxymethyl cellulose, polyethylene glycol, polyvinyl alcohol, polypropylene glycol, polylactic acid, and polycaprolactone.

3. The method for preparing porous silk fibroin microspheres according to claim 1, wherein: In the mixed solution of step S2, the volume ratio of the silk fibroin solution to the inducer aqueous solution is 1:(0.25-5); wherein the mass fraction of the silk fibroin is 0.5-5%, and the mass fraction of the inducer is 0.5-5%.

4. The method for preparing porous silk fibroin microspheres according to claim 1, wherein: The mass percentage of the silk fibroin solution is 1-10 wt %, and the mass percentage of the inducer aqueous solution is 1-10 wt %.

5. The method for preparing porous silk fibroin microspheres according to claim 1, wherein: The drying treatment method is natural drying or vacuum drying at 37 to 60° C., or freeze drying under reduced pressure at -45 to -60° C.

6. The method for preparing porous silk fibroin microspheres according to claim 1, wherein: In step S3, during the concentration-film forming treatment, the temperature is 10-120° C. and the time is at least 6 hours.

7. The method for preparing porous silk fibroin microspheres according to claim 1, wherein: The method also includes soaking the obtained porous silk fibroin microspheres in ethanol, then centrifuging to remove the ethanol, and adding water to resuspend the microspheres twice.

8. A porous silk fibroin microsphere, characterized in that: The porous silk fibroin microspheres are prepared according to the preparation method according to any one of claims 1 to 7.

9. The porous silk fibroin microspheres according to claim 8, characterized in that: The porous silk fibroin microspheres are regular spherical or nearly spherical, with a particle size ranging from 3 to 15 μm; the surface has a porous structure, and the pore size is within 500 nm.

10. Use of the porous silk fibroin microspheres according to any one of claims 8 to 9, characterized in that: The porous silk fibroin microspheres are used in the fields of cell culture carriers, drug delivery systems, and protein separation and purification.

Citation Information

Patent Citations

  • Strontium-doped porous silk fibroin microsphere and preparation method thereof

    CN108553690A